The Role of Social Media Analytics in Integrated Marketing Communication and Understanding Consumer Behaviour: The Pathway to Optimal Customer Relationship Management - Valentin Kuleto; Vladimir Matovic; Biljana Ilic; Svetlana Jokic; Mladen Radakovic (International Journal of Electronics Automation, 2023)
This study explores the role of social media analytics in understanding consumer behavior within the context of Integrated Marketing Communication (IMC). Businesses now have access to a lot of data thanks to the spread of social media platforms, which can give them important insights into consumer preferences, attitudes, and behaviors. This study discusses the methodologies and tools used in social media analytics and how they can be leveraged to enhance IMC strategies and better understand consumer behavior. The study communicates the main topics of the research: social media analytics, integrated marketing communication, consumer behavior, and customer relationship management. It also suggests a connection between these topics, which is that social media analytics can enhance integrated marketing communication efforts, leading to a better understanding of consumer behavior and, ultimately, improved customer relationship management.
Keywords: Social media analytics; business strategy; consumer behaviour; customer relationship management; data analysis; digital marketing; integrated marketing communications